DFT Study of Xenon Complexes Adsorption on Graphene and Metal Embedded Graphene - Huang, Bin; Yuan, Dingzhong; Chen, Bibo (Asian Journal of Chemistry, 2013)
In this paper, periodic density functional theory calculations have been performed to study the adsorption of xenon complexes on intrinsic, Pt-doped and Cu-doped graphene sheets, respectively. Compared with the intrinsic graphene, metal doped graphene can strongly adsorb xenon atom and xenon complexes with higher binding energy value and shorter distance between the xenon atom and the graphene surface. Furthermore, we also demonstrate that the adsorption of XeF and XeBeO on metal doped graphene sheet are dissociation adsorption modes due to their high dipole moment. The density of states (DOS) results and the electronic density difference image indicate that the xenon complexes were strongly adsorbed on metal doped graphene by orbital hybridization, but no evidences for the hybridization between xenon complexes and intrinsic graphene sheet. We believe our calculations are useful to understand available experimental results.